Highly Elastic and Conductive Human‐Based Protein Hybrid Hydrogels. Issue 1 (9th November 2015) - Annabi, Nasim; Shin, Su Ryon; Tamayol, Ali; Miscuglio, Mario; Bakooshli, Mohsen Afshar; Assmann, Alexander; Mostafalu, Pooria; Sun, Jeong‐Yun; Mithieux, Suzanne; Cheung, Louis; Tang, Xiaowu (Shirley); Weiss, Anthony S.; et al.
Abstract : A highly elastic hybrid hydrogel of methacryloyl‐substituted recombinant human tropoelastin (MeTro) and graphene oxide (GO) nanoparticles are developed. The synergistic effect of these two materials significantly enhances both ultimate strain (250%), reversible rotation (9700°), and the fracture energy (38.8 ± 0.8 J m −2 ) in the hybrid network. Furthermore, improved electrical signal propagation and subsequent contraction of the muscles connected by hybrid hydrogels are observed in ex vivo tests.